Nunavut Photo Essay - North America, Arctic Institute of (ARCTIC, 1999)
To celebrate the creation of Nunavut on 1 April 1999, we've gathered together a collection of photographs of Canada's newest territory from friends, staff, and research associates of the Arctic Institute. In future issues of InfoNorth, we will present selections of photographs from Canada's other territories. Many thanks to our contributors: J. Crump, M. Goodjohn, G. Holdsworth, R. MacDonald, T. Nail, D.G. Reid, P. Schledermann, and D. Stenton. .